O uso dos sistemas de informação geografica (SIGs) na odontologia : aplicação no municipio de Piracicaba, SP - Pereira-Dourado, Stela Márcia, 1980- (2008)
Orientadores: Antonio Carlos Pereira, Glaucia Maria Bovi Ambrosano, Carlos Alberto Vettorazzi